The standard of care for alternative medicine practitioners: legal problems and challenges - Jahn Kassim, Puteri Nemie (2010)
The use of alternative medicine has becoming increasingly popular amongst the Malaysian population. However, the increased number of alternative medicine practitioners has developed a pressing concern amongst relevant stakeholders on a variety of legal issues. At the moment, practices of alternative medicine in Malaysia are not governed by any specific legislation. Although some laws may have an indirect effect on these practices but they are not adequate to ensure comprehensive protection to relevant parties. The main problem is defining the appropriate standard of care for these practices in order to be at par with the standard of care of conventional medicine practitioners. Defining a proper standard of care is a crucial and necessary step in the integration of alternative medicine into conventional medicine and help in the facilitation of uniform licensure and accreditation in this growing industry.